Developing dynamic web pages using template and non-template: A descriptive analysis - Saad, Mohd. Nizam; Omar, Mohd. Adan; Abdul Mutalib, Ariffin; Hussain, Azham (Östereichische Computer Gesellschaft, 2005)
World Wide Web has composed a lot of content on the Internet since its existence. Although the web has mature, there are still Websites in static behavior, causing the content hard to update. Nowadays, web pages with fresh content are very important to attract users. Hence, Websites should be transformed into dynamic pages to ensure only latest information is displayed. Currently a good templating system is the best solution to do the transformation. In this paper we present the result of a comparison for developing and maintaining a dynamic websites using a template and using non-template. Two groups of students were studied: the first group required to develop a dynamic website using template while the second group develops the same website using non-template approach. The aim of both tasks is to compare the time taken by both groups to complete all the given tasks. The research found that although more time needed to create a template however it help decreasing the time taken to maintain the content of dynamic websites. This result shows that template can improve the development cycle of a website especially maintaining the dynamic web pages.